ECO-FRIENLY SYNTHESIS OF GOLD NANOPARTICLES AND STUDY THEIR EFFECT WITH ANTIBIOTICS AGAINST ACINETOBACTER BAUMANNII - & et al., Al-Shaabani (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This study was aimed to produce AuNPs biologically using Klebsiella pneumoniae and study their synergistic effect with some antibiotics.Technologies of nanoparticles are quick and are employed in many applications in biomedicine. The potential of metallic nanoparticle as an anti-microbial agent is greatly investigated which considered as an alternative method to reduce the challenges of multi-drug resistance microbes. The present study discusses the novel approach to synthesize nanoparticles involving eco-friendly synthesis of gold nanoparticles using Klebsiella pneumoniae and study their effect as antimicrobial spectrum .Also study synergism effect of gold nanoparticles with antibiotic against Acinetobacter baumannii. These approaches are used to enhance antimicrobial efficacy of nanoparticles by modification of surfaces and to investigate activity of antibiotic delivery.